Scribal intent: sociocultural appropriation of the Testament of Abraham in eighteenth-century Romanian lands - Roddy, Nicolae (The journal of religion & society, 1999)
This paper focuses on the circulation of the Testament of Abraham (TAbr) within its Romanian sociohistorical context in an effort to determine how it is this first-century Alexandrian Jewish narrative found cultural relevance in eighteenth-century Romanian society. Textual analysis shows this Greek apocryphon to have been thoroughly "romanianized," reflecting a high degree of interaction between its narrative and social worlds. TAbr circulated outside the monasteries, suggesting that monks intended this text to be read by members of the literate boier, or noble class, who might find in Abraham the model of an exemplary "noble man" and remember the impoverished populace living on their own estates.